The simultaneous removal of cadmium (II) and lead (II) from wastewater with the application of green synthesized magnesium silicate hydrate - Qing, Zhang; Guijian, Liu; Shuchuan, Peng; Chuncai, Zhou (Frontiers in Earth Science, 2023)
To the purpose of solving the problems of coal-gangue accumulation in the mine and pollution of cadmium (II) and lead (II) in wastewater, magnesium silicate hydrate (M-S-H) was synthesized from coal-gangue by thermochemical. M-S-H had removed Cd(II) and Pb(II) by adsorption. The characterization of M-S-H and adsorption effects factors, including initial solution pH, initial metal concentration, adsorbent dose, temperature, reaction time, and coexisting ions were explored for adsorption performance. The solution pH was precisely controlled by a pH meter. The adsorption temperature was controlled by a thermostatic gas bath oscillator with an error of ± 0.3. These results from this study revealed that M-S-H surface area increased from 8.12 to 26.15 m2/g with a pore volume of 0.12 cm3/g. The maximum adsorptions of Cd(II) and Pb(II) by M-S-H were 59.52 and 83.33 mg·g-1, respectively. The adsorption performance for Cd(II) and Pb(II) reached saturation at pH 5, temperature 25℃, M-S-H 6 g/L, reaction time 90 min, and metal concentration 300 mg/L. Cd(II) and Pb(II) adsorption were spontaneous and endothermic and well fitted with the pseudo-second-order kinetic and Langmuir isotherm adsorption models. The adsorption mechanisms were electrostatic interaction, ion exchange, and surface complexation. This research indicated that the synthesized M-S-H from coal gangue was efficiently eliminated metal ions from water, opening up new possibilities for coal gangue reuse.